2022
DOI: 10.1038/s41598-022-08440-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ocular tumors through a novel applicator on a conventional proton pencil beam scanning beamline

Abstract: Treatment of ocular tumors on dedicated scattering-based proton therapy systems is standard afforded due to sharp lateral and distal penumbras. However, most newer proton therapy centers provide pencil beam scanning treatments. In this paper, we present a pencil beam scanning (PBS)-based ocular treatment solution. The design, commissioning, and validation of an applicator mount for a conventional PBS snout to allow for ocular treatments are given. In contrast to scattering techniques, PBS-based ocular therapy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Recently, Regmi et al reported lateral penumbras at 1 mm depth ranging from 2.6-3.6 mm with their spot scanning system. 11 While a strict comparison is difficult since these parameters are dependent on factors such as target size and depth, the results obtained using the aperture developed in this work are firmly within these ranges.In a spot scanning system the distal penumbra is dominated by the highest energy layer used. As seen in Figure 3a, the highest energy expected to be used with this system is 121.0 MeV, which has a D80 of 61 mm and a 90%−10% distal fall-off of 2.4 mm.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Recently, Regmi et al reported lateral penumbras at 1 mm depth ranging from 2.6-3.6 mm with their spot scanning system. 11 While a strict comparison is difficult since these parameters are dependent on factors such as target size and depth, the results obtained using the aperture developed in this work are firmly within these ranges.In a spot scanning system the distal penumbra is dominated by the highest energy layer used. As seen in Figure 3a, the highest energy expected to be used with this system is 121.0 MeV, which has a D80 of 61 mm and a 90%−10% distal fall-off of 2.4 mm.…”
Section: Discussionsupporting
confidence: 51%
“…The aperture system developed in this work was designed to treat ocular sites on a gantry-based spot scanning proton beam. While at least two institutions have previously reported the ability to treat ocular sites with a non-dedicated eyeline, 10,11 the majority of centers are treating ocular sites in fixed beam rooms with a dedicated eyeline. The aperture system presented here demonstrates the possibility of treating ocular sites on an existing clinical spot scanning proton gantry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations